Evaluation of Neolamarckia Cadamba (Roxb.) Bosser Leaf Extract on Glucose Tolerance in Glucose-Induced Hyperglycemic Mice - Ahmed, Firoz (African Networks on Ethnomedicines, 2010)
Neolamarckia cadamba (Rubiaceae) leaf is used in folk medicine of Bangladesh for the treatment of diabetes, but so far no scientific study has been done which may support its use in traditional medicine. The present study was carried out to evaluate the possible glucose tolerance efficacy of methanolic extract of Neolamarckia cadamba leaf using glucose-induced hyperglycemic mice. The extract at different doses was administered one hour prior to glucose administration and blood glucose level was measured after two hours of glucose administration (p.o.) using glucose oxidase method. The statistical data indicated significant oral hypoglycemic activity on glucose-loaded mice at the two highest doses of 200 and 400 mg extract per kg body weight. Maximum anti-hyperglycemic activity was shown at 400 mg per kg body weight, which was comparable to that of, glibenclamide (10 mg/kg). The methanolic extract of leaf of Neolamarckia cadamba had beneficial effects in reducing the elevated blood glucose level of hyperglycemic mice.